Bone scintigraphy and clinical outcome in rheumatoid gonarthritis - Schwarz, A.; Elbracht, T.; Jeschke, A.; Weseloh, G.; Swoboda, B.; Kuwert, T. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: For evaluation of the effect of radiosynoviorthesis (RSO) on the early and delayed uptake of 99mTc-biphosphonates and its relation to clinical outcome we studied these variables before and after radiosynoviorthesis performed on 41 knees affected by rheumatoid arthritis. Method: Thirty-seven patients with rheumatoid gonarthritis were treated by intraarticular injection with 185 MBq yttrium-90 citrate. In four of them both knees were treated so that 41 therapies were evaluated. On the average 35 days before and 120 days after radiosynoviorthesis, the early and delayed uptake of 99mTc-diphosphonate (DPD) was measured with a planar gamma camera. Early and late DPD uptake was quantified as a ratio between count values derived from rectangular ROIs placed on the knee treated and on the ipsilateral thigh. The severity of clinical symptoms was assessed on two 3-point rating scales averaged. Results: 30 of the 41 cases favorably responded to radiosynovior-thesis. There was a significant correlation between clinical outcome and pretherapeutic early DPD uptake (EDU) (p <0.05), but not between outcome and pretherapeutic late DPD uptake (DDU). In the whole group, EDU decreased in approximately 76% of cases after therapy (p <0.05), DDU in 54% (p >0.05). In 25 of the 30 responders EDU decreased; EDU increased or remained constant in five of the eleven non-responders. The correlation between outcome and the difference in EDU was significant (r = 0.344; p <0.05). There was no such significant relationship between the difference between pre- and posttherapeutic DDU and clinical course. Conclusion: Three-phase bone scintigraphy may contribute to predict and assess the success of radiosynovior-thesis in rheumatoid arthritis of the knee joint.
Keywords: Radiosynovectomy; bone scintigraphy; rheumatoid arthritis